Caterpillar-Induced Rice Volatile (E)-β-Farnesene Impairs the Development and Survival of Chilo suppressalis Larvae by Disrupting Insect Hormone Balance - Yang, Lei; Yao, Xiaomin; Liu, Baosheng; Han, Yangchun; Ji, Rui; Ju, Jiafei; Zhang, Xiaona; Wu, Shuwen; Fang, Jichao; Sun, Yang (Frontiers in Physiology, 2022)
Significant research progress has recently been made on establishing the roles of tps46 in rice defense. (E)-β-farnesene (Eβf) is a major product of tps46 activity but its physiological functions and potential mechanisms against C. suppressalis have not yet been clarified. In the present study, C. suppressalis larvae were artificially fed a diet containing 0.8 g/kg Eβf and the physiological performance of the larvae was evaluated. In response to Eβf treatment, the average 2nd instar duration significantly increased from 4.78 d to 6.31 d while that of the 3rd instar significantly increased from 5.70 d to 8.00 d compared with the control. There were no significant differences between the control and Eβf-fed 4th and 5th instars in terms of their durations. The mortality rates of the 2nd and 3rd Eβf-fed instars were 21.00-fold and 6.39-fold higher, respectively, than that of the control. A comparative transcriptome analysis revealed that multiple differentially expressed genes are involved in insect hormone biosynthesis. An insect hormone assay on the 3rd instars disclosed that Eβf disrupted the balance between the juvenile hormone and ecdysteroid levels. Eβf treatment increased the juvenile hormones titers but not those of the ecdysteroids. The qPCR results were consistent with those of the RNA-Seq. The foregoing findings suggested that Eβf impairs development and survival in C. suppressalis larvae by disrupting their hormone balance. Moreover, Eβf altered the pathways associated with carbohydrate and xenobiotic metabolism as well as those related to cofactors and vitamins in C. suppressalis larvae. The discoveries of this study may contribute to the development and implementation of an integrated control system for C. suppressalis infestations in rice.